MRONJ with Current Diagnostic and Treatment Approaches - Öçal, Mustafa Çağdaş; Baybars, Sümeyye Coşgun; Duran, Merve Hacer (My University, 2024)
Medication Related Osteonecrosis of Jaw (MRONJ) is a persistent and rare pathology that develops with progressive bone destruction and bone necrosis as a result of impaired blood supply in the mandible and maxilla. The key point to the prevention and treatment of MRONJ is screening high-risk patients predisposed to the disease to detect it at an early stage to effectively prevent the risk of progression and occurrence. Although no exposed bone is seen in clinical examination, osteonecrosis can be diagnosed early by radiographic examination. Therefore, advanced imaging techniques are important in the early diagnosis of MRONJ. There is no defined gold standard treatment in the literature and the treatment of MRONJ is often very difficult. Treatment strategies are mainly focused on minimizing the progression or formation of bone necrosis, eliminating pain, controlling infection and optimizing the patient's quality of life. American Association of Oral and Maxillofacial Surgeons (AAOMS) recommends stage-based treatment planning in MRONJ patients. In addition to the treatment methods recommended by the AAOMS, there are research showing that some adjuvant treatments have a positive effect on recovery in MRONJ patients. For example, the use of platelet-rich plasma/fibrin in addition to surgical treatment increasing the success of surgery is one of them. Alternative treatment options are low-level laser therapy, surgical debridement with laser, surgical debridement under the guidance of fluorescent staining method, use of platelet concentrates, ozone and hyperbaric oxygen therapy, pentoxifylline, alpha-tocopherol, photo-bio modulation, use of parathormone or stem cell transplantation into the lesion. In this review, we aimed to update the knowledge, attitudes and behaviors of dentists about MRONJ and to shape the approach to MRONJ with the guidance of current literature.
Keywords: Treatment; Diagnosis; Medication-related osteonecrosis of the jaw